Practical woodwork for laboratory technicians - Eyers, A. S. (Oxford, N.Y., Pergamon Press, 1970)
Practical Woodwork for Laboratory Technicians serves as a guide for technicians and workers in maintaining laboratories and workshops and in the production of apparatus for demonstration and research. It contains a number of projects that are useful both in the workshop and the laboratory. The book begins by discussing the importance of timber. It then describes the tools used in woodwork construction such as saws, chisels, marking gauges, hammers, boring tools, cramps, and holding devices, and similar tools. It also illustrates planing of wood, marking and testing boards, drawing geometrical.
Index and bibliography at the end
Keywords: Woodwork; Woodworking machinery